BUDAYA BELAJAR SISWA PADA SEKOLAH UNGGUL DI SMA NEGERI 1 PAMEKASAN - Saiful Arif (Research Institute and Community Engagement of IAIN MADURA, 2011)
Eminent School is school developed to reach the excellence in output (output) its education, and to reach the the excellence, hence, input ( input), education process, teacher and instructor, management, education service, with its supporter medium have to be instructed to support reaching of that target. This research describes about 3 (three) important matters which become fundamental study at this research, that is: ( 1) how does it plan the study activities capable to grow learning culture to excellence? ( 2) how does each individuals use the strategy to reach for successfulness in learning as learning cultural implementation ? ( 3) how does it realize the excellence norm to grow the learning culture ? Research method that is used is qualitative desain with etnografis approach trying to describe the cultural specially habit of student learning to become eminent mankind in learning. The Research result that is obtained is; a) started from construction process at the time of new MOS student, exploiting of self - learning sources, giving] of self-supporting duties by teacher to student through LKS. b) the strategy that is used is started from construction process at the time of new MOS, exploiting of self - learning sources, giving] of self-supporting duties by teacher to student through LKS. c) there are structural relation pattern and horizontal between student, teacher, headmaster in the form of values transmitted in developing eminent academic atmosphere at study process